Ravidas Ki Vaani Me Manavvaad: Exploring Humanism in the Teachings of Ravidas (Journal of Advances and Scholarly Researches in Allied Education, 2014)
ekuookn vaxzsth Hkk"kk dsßáweSfuTeÞ (Humanism) dk fgUnh :ikUrj gSA1 áweSfuTe 'kCn dh mRifr ySfVu Hkk"kk áwEul* ls gqbZ gSA bl izdkj^áweu* 'kCn esa ^bTe* izR;; yxus ls ßáweSfuTeÞ vFkkZr ekuookn 'kCn dh mRifrgqbZA